FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN MAKROSITOSIS PADA PASIEN HIV/AIDS YANG MENDAPAT TERAPI ZIDOVUDIN DI RUMAH SAKIT SANGLAH DENPASAR - Ridana Wibawa, Ketut; Parwati Merati, Tuti; Somia, Agus; Utama, Susila (journal of internal medicine, 2010)
Zidovudine is a Þ rst line drug used for treating HIV/AIDS patients in Indonesia and has been associated with prolongedsurvival, a reduction in the frequecy and severity of opportunistic infections, transient increases in the number of CD4 Tlymphocytes, and decreases in serum HIV p24 antigen. However prolong use of zidovudine associated with bone marrowtoxicity manifested by macrocytosis until anemic condition which need the transfusion. Some factors has been identiÞ ed canincreasing the bone marrow toxicity like: age, sex, cotrimoxazole, anemic and neutropenia condition, CD4 count < 200 cells/ L,vit B12 and folic acid level.To determine the risk factors correlated with incident of macrocytosis on HIV/AIDS patients treated with zidovudine,an analytical retrospective cross sectional study was done. The patients were selected using WHO criteria and the antiretoviraltherapy as Depkes guideline which zidovudine base with dose 600 mg/day. The age, sex, cotrimoxazole use and CD4 count wereassesed from all the patients by review medical record when the macrocytosis exist.This study included 140 subyects, age arround 19 ! 65 years old, sex male 72 % and female 28%. Cotrimoxazole use as atreatment or prophylaxis for PCP infection is 90% and the median CD4 count is 24.5 cells/ L. The incidence of macrocytosis is54.3% which is 46.4% without anemia and 7.9% present with anemia. The mean MCV value before zidovudine therapy is 86.27fL and elevated to 110.11 fL after zidovudine therapy. The median time of macrocytosis is 5 month. With bivariat analysis wedidn"t Þ nd correlation betwen age, sex, cotrimoxazol use and CD4 count with incident of macrocytosis (age p = 0.935 95% CIOR = 0.963 sex p = 0.800 95% CI OR = 0.846 cotrimoxazol use p = 0.237 95% CI OR = 0.403 and CD4 count p= 0.646 95%CI = 0.997 respectively).This study concluded no correlation betwen age, sex, cotrimoxazol use and CD4 count with incident of macrocytosis onHIV/AIDS patients whom treated with zidovudine. We suggest to routinely monitoring the MCV value every a month in a year,be cause the incidence of macrocytosis cause by toxicity effect of zidovudine to bone marrow is high.